Mesmerized by Mantra: Gregory Maskarinec and Nepali Shaman Oral Text - Subedi, Bamdev (Dhaulagiri Journal of Sociology and Anthropology, 2023)
A cursory review of the literature shows that shamanism as traditional healing has been a subject of scholarly interest. Many foreign scholars have studied the Nepali shamans and their healing practices. Professor Gregory G. Maskarinec is known for his in-depth ethnographic study of the oral texts of Nepali shamans. He explored the shamanic world, particularly the meaning of mantras shamans use to diagnose and treat affliction, and published books on Nepalese Shaman Oral Texts. He was honored by Birendra Pragyalankar, a prestigious award given to foreign scholars for their scholarly contributions. Maskarinec, a professor in the Department of Family Medicine and Community Health at the University of Hawaii, passed away from cancer on June 16, 2022, at 71. He is no longer with us but will be remembered for his contributions. This paper examines the relevance of traditional healing in light of Professor Maskarinec's work on Nepali shamans.